2017
DOI: 10.1038/srep43166
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of long non-coding RNAs highlights their spatio-temporal expression patterns and evolutional conservation in Sus scrofa

Abstract: Despite modest sequence conservation and rapid evolution, long non-coding RNAs (lncRNAs) appear to be conserved in expression pattern and function. However, analysis of lncRNAs across tissues and developmental stages remains largely uncharacterized in mammals. Here, we systematically investigated the lncRNAs of the Guizhou miniature pig (Sus scrofa), which was widely used as biomedical model. We performed RNA sequencing across 9 organs and 3 developmental skeletal muscle, and developed a filtering pipeline to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 55 publications
19
56
0
Order By: Relevance
“…Similar to previous reports 1,8,17,23,28 , we discovered that lncRNAs identified in our study 222 exhibited typical characteristics of lncRNAs found in other species including vertebrates 7 . Such 223 characteristics are lower GC content, shorter in length, and low sequence conservation even among 224 closely related species.…”
Section: Ae Aegypti Lncrnas Were Differentially Expressed Following supporting
confidence: 91%
“…Similar to previous reports 1,8,17,23,28 , we discovered that lncRNAs identified in our study 222 exhibited typical characteristics of lncRNAs found in other species including vertebrates 7 . Such 223 characteristics are lower GC content, shorter in length, and low sequence conservation even among 224 closely related species.…”
Section: Ae Aegypti Lncrnas Were Differentially Expressed Following supporting
confidence: 91%
“…To maximize the use of splice‐site information, a two iteration mapping strategy was used as in our previous study . In the first iteration, paired‐end clean reads were mapped to the reference genome of Sus scrofa (v10.2) using TopHat2 (v2.1.0) in a reference‐based approach.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, 29% of the former were detected only in one cell line compared to 7% of the latter [3]. Highly cell-type-and temporal-specific lncRNA expression patterns have also been shown in vivo [184][185][186][187]. Analyses of patterns of expression of various lncRNAs in mammalian brains based either on in situ hybridization [184] or RNA-seq analysis [185] revealed highly restricted patterns confined to neuroanatomical regions, cell types, or subcellular compartments in a genderdependent fashion.…”
Section: Subtle Effectsmentioning
confidence: 97%